2007
DOI: 10.1091/mbc.e06-12-1162
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Interaction of Cyclin G–associated Kinase with Adaptor Protein 1 Regulates Lysosomal Enzyme Sorting

Abstract: The adaptor protein 1 (AP1) complex is a heterotetramer that participates in cargo sorting into clathrin-coated vesicles at the trans-Golgi network (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 63 publications
(110 reference statements)
8
82
0
Order By: Relevance
“…In addition to having a kinase domain, GAK is highly homologous with neuron-specific auxilin, which plays a pivotal role in clathrin-dependent trafficking in neural cells. As expected from this structural similarity, the ubiquitously expressed GAK protein localizes to the trans-Golgi network (TGN) and is an essential cofactor for Hsc70-dependent uncoating of clathrin-coated vesicles in many non-neural cells (Korolchuk and Banting, 2002;Kametaka et al, 2007). Indeed, clathrin-mediated endocytosis is partially blocked in GAK-knockdown cells, and the J domain of GAK was found to be important for this event (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…In addition to having a kinase domain, GAK is highly homologous with neuron-specific auxilin, which plays a pivotal role in clathrin-dependent trafficking in neural cells. As expected from this structural similarity, the ubiquitously expressed GAK protein localizes to the trans-Golgi network (TGN) and is an essential cofactor for Hsc70-dependent uncoating of clathrin-coated vesicles in many non-neural cells (Korolchuk and Banting, 2002;Kametaka et al, 2007). Indeed, clathrin-mediated endocytosis is partially blocked in GAK-knockdown cells, and the J domain of GAK was found to be important for this event (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…In addition to its role in endocytosis, GAK has been implicated in delivering lysosomal proteins from TGN (Hirst et al, 2008;Kametaka et al, 2007;Lee et al, 2005;Zhang et al, 2005). In Drosophila, although the importance of clathrinmediated endocytosis in cell-cell signaling and cell morphogenesis RESEARCH ARTICLE Development 138 (6) is well known, the roles of clathrin-dependent transport from organelles in development are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as we have previously shown that clathrin forms aggregates in aux mutant cells (Kandachar et al, 2008), it is possible that clathrin in these aggregates is incapable of interacting with AP-1. Kametaka et al (Kametaka et al, 2007) have shown that, in HeLa cells, AP-1 recruits GAK to TGN, and the presence of GAK at the TGN is required for lysosomal trafficking. It is possible that, in Drosophila germ cells, localization of Aux to the Golgi also relies on AP-1 and this recruitment is required for formation of CCVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations